Perspectives of Major World Religions regarding Euthanasia and Assisted Suicide: A Comparative Analysis - Grove, Graham (Journal of religion and health, 2022)
Euthanasia and physician-assisted suicide (EPAS) are important contemporary societal issues and religious faiths offer valuable insights into any discussion on this topic. This paper explores perspectives on EPAS of the four major world religions, Christianity, Islam, Hinduism and Buddhism, through analysis of their primary texts. A literature search of the American Theological Library Association database revealed 41 relevant secondary texts from which pertinent primary texts were extracted and exegeted. These texts demonstrate an opposition to EPAS based on themes common to all four religions: an external locus of morality and the personal hope for a better future after death that transcends current suffering. Given that these religions play a significant role in the lives of billions of adherents worldwide, it is important that lawmakers consider these views along with conscientious objection in jurisdictions where legal EPAS occurs. This will not only allow healthcare professionals and institutions opposed to EPAS to avoid engagement, but also provide options for members of the public who prefer an EPAS-free treatment environment.